MASYARAKAT UTOPIS DAN DISTOPIS DALAM TEKS THE ONES WHO WALK AWAY FROM OMELAS, KARYA URSULA LE GUIN - Rosaliza, Mita; Syam, Essy (Jurnal Ilmu Budaya, 2018)
This writing analyzes a short story entitles The Ones Who Walk Away From Omelas written by Ursula Le Guin which highlights the elements of Utopia and Dystopia found in a society as reflected in the text such as the happiness, cheerfulness which are almost perfect. Besides, the feeling of secure is also felt by the inhabitants of Omelas so that they don’t need a government to manage their life. On the contrary, the element of dystopia is ironic, in which the happiness felt by the people is paid by a little child who is locked in dark, small room. This child is victimized to guarantee the perfect life of the people in Omelas. Consequently, those who can’t accept this reality decide to leave Omelas, they are the ones who walk away from Omelas. Related to that, this analysis applies descriptive analysis in which the result will be explained descriptively. From the description, it will show how the elements of Utopia and Dystopia are reflected in the life of the people in Omelas which describe the society of Omelas and its belief in Sacrificing the child for the sake of the happiness of the community.